Herder-farmer conflict in sub-Saharan Africa and corporate social responsibility in Nigeria's oil host communities - Joseph Ikechukwu Uduji; Nduka Elda Vitalis Okolo-Obasi; Joy Ukamaka Uduji; Longinus Chukwudi Odoh; Deborah Chinwendu Otei; Ozioma Happiness Obi-Anike; Emmanuel Ejiofor Nwanmuoh; Kristopher Onyekachi Okezie; Oliver Uzonna Ngwuoke; Benjamin Uchemefuna Ojiula; Samuel Chukwuemeka Ezuka; Rollins Chiyem Iyadi (African Governance and Development Institute (AGDI), 2024)
There have been increasing demands on multinational oil companies (MOCs) to provide community development programmes and security to their host communities in Nigeria. This is mainly because developmental projects and security are lacking in most of these communities and most of the time they are not provided by government. Thus, we set out to examine the impact of MOCs' Corporate Social Responsibility (CSR) model on cutting the main drivers cum prompters of herder-farmer violence in the Niger Delta expanse of Nigeria. Results from the use of both propensity score matching and logit model indicate that, though, a very skimpy part of the CSR intervention are specifically aimed at alleviating herder-farmer conflict, the CSR has made momentous impact in the drops in land deprivation, social disparities, pressure over land as well as bettering people's lives in the region. The finding suggests that MOCs are well positioned to tackle the drivers and triggers of farmer-herder violence, when investment in cluster development boards (CDBs) is designed to improve land management infrastructure, train local leaders in dispute resolution techniques, and prioritize trust between communities and the security forces. This implies that business has an obligation to help in solving problems of public concern.
Keywords: 330; Herder-farmer conflict; corporate social responsibility; multinational oil companies; sub-Saharan Africa